Keloid Scars: A Comprehensive Review of Pathophysiology, Aetiology, and Therapies - Katanyutanon, Papichaya; Pawanpat Katanyutanon (International Journal of Medical Science and Clinical Research Studies, 2025)
This is an integrative review of the literature which analyses the studies of treatments of keloid scars, touching on the pathophysiology and aetiology of the scars. The paper explores all the different aetiology which could lead to keloid scars such as genetics, inflammatory cells and growth factors including Tenasin C, TGF-β1 and β2; all the risk factors which cause the scars; an in-depth detail of all the pathways and protein alteration of the scars such as extracellular matrix proteins and ECM-associated proteins; the epigenetics of keloid scarring including DNA methylation and histone modifications. In addition to this, the paper ended with a detailed analysis of the different treatments for keloid scarring including surgery, radiotherapy, interferons, botulinum toxins and bleomycin. These findings showed that while there are many hypotheses regarding the pathophysiology and aetiology of the keloid scars by understanding the protein alteration and pathways, many scientists have created adequate treatments for it. With the current advancement, the treatments all have their own limitations but this study aims to summarise each limitation to provide pathways to best treat the keloid scars.